An earthquake casualty prediction method considering burial and rescue. (June 2020) - Fang, Zhiming; Huang, Jiahao; Huang, Zhongyi; Chen, Lingzhu; Cong, Beihua; Yu, Liying
Highlights: A seismic casualty prediction method that considers the rescue process is constructed. In this method, a seismic network model with a dynamic rescue rate is built. The optimal rescue plan can be obtained by solving the seismic network model. The optimal rescue plan can minimize the casualties of earthquake. Abstract: To predict the impact of the rescue work on the casualties after the earthquake, a seismic casualty prediction method that comprehensively considers the burial situation and the rescue process is constructed. In this method, a seismic network model based on the graph theory method is built, then the burial situation on an area of after an earthquake can be quickly calculated by using the calculation method of casualty rate based on the building damage rate. Finally, the optimal rescue plan can be obtained by solving the objective function of the seismic network model through the genetic algorithm. Taking the 1100 campus of University of Shanghai for Science and Technology as a case, the burial situation and the casualties under the influence of the rescue work are analyzed after assuming a Ⅹ-degree earthquake occurs on this area, based on which an optimal rescue plan is proposed. After that, by comparing with two shortest path methods, the superiority of the proposed method is highlighted. This method can be used as the basis for regional earthquake risk assessment and emergency rescue plans establishment, and it can also be used as a tool for generating optimal rescue routes after the earthquake.